(untitled) (Journal of Oriental Studies, 2018)
The article considers the role of the Shanghai Cooperation Organization in reviving the Silk Road. The need to establish the Shanghai Cooperation Organization and develop its activities based on the “Shanghai spirit” – good-neighborliness, mutual trust and friendship, the importance of the organization’s activities in the system of international relations and cooperation between the SCO member states, the prospects for linking the activities of the Shanghai Cooperation Organization and the initiative of the Silk Road Economic Belt.